2017
DOI: 10.7196/samj.2017.v107i7.12309
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of chemotherapy-induced neutropenia in HIV-infected and uninfected patients with breast cancer receiving neoadjuvant chemotherapy

Abstract: Background. Chemotherapy-induced neutropenia (CIN) can result in poor tolerance of chemotherapy, leading to dose reductions, delays in therapy schedules, morbidity and mortality. Actively identifying predisposing risk factors before treatment is of paramount importance. We hypothesised that chemotherapy is associated with a greater increase in CIN and its complications in HIV-infected patients than in those who are not infected. Objective. To establish the incidence of CIN in HIV-infected and uninfected patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 29 publications
4
20
1
Order By: Relevance
“…In addition to further survival studies, research needs to address side‐effects and survivorship, with relevant studies currently underway . Clinically, concerns have been raised related to delays in initiating primary or adjuvant chemotherapy in highly immuno‐suppressed patients, HAART‐chemotherapy interactions, and a higher incidence of intolerance to, and side‐effects of, chemotherapy, including chemotherapy‐induced neutropenia, which are often exacerbated in the HIV‐positive cancer patient . In palliative care patients in South Africa and Uganda, Selman et al .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to further survival studies, research needs to address side‐effects and survivorship, with relevant studies currently underway . Clinically, concerns have been raised related to delays in initiating primary or adjuvant chemotherapy in highly immuno‐suppressed patients, HAART‐chemotherapy interactions, and a higher incidence of intolerance to, and side‐effects of, chemotherapy, including chemotherapy‐induced neutropenia, which are often exacerbated in the HIV‐positive cancer patient . In palliative care patients in South Africa and Uganda, Selman et al .…”
Section: Discussionmentioning
confidence: 99%
“…5,34,53,59,73,74,80-82 In the ONCOVIH study (France), consisting of 21 BCs in WLWHA, the median CD4 cell count was 347 cells/mm 3 (range: 180-1039), 51 while in Durban, South Africa the median CD4 count was 435 cells/mm 3 (range 80-945). 77 BC in WLWHA is certainly not associated with a low CD4 count 34 implying that the degree of immune-compromise does not correlated with tumorigenesis. 82…”
Section: Clinical and Pathological Characteristics Of Bc In Plwhamentioning
confidence: 99%
“…9 More recent legitimately credible studies from SSA also demonstrated no statistically significant difference in the stage at presentation, histologic subtype, tumor grade, or nodal involvement between HIV-positive groups and the other groups. 7,75,77,86…”
Section: Clinical and Pathological Characteristics Of Bc In Plwhamentioning
confidence: 99%
See 2 more Smart Citations